Sociology and theology : alliance and conflict - Martin, David, 1929-2019; Mills, John Orme; Pickering, W. S. F. (Brill, 2004)
This work brings together two disciplines. Both sociology and theology give an account of the human condition, but the majority of sociologists and theologians have dismissed each other's views as irrelevant.